Fragmented many-body states of definite angular momentum and stability of attractive three-dimensional condensates - Tsatsos, Marios; Streltsov, Alexej Iwanowitsch; Alon, Ofir E.; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2010)
A three-dimensional attractive Bose-Einstein condensate is expected to collapse when the number of the particles N in the ground state or the interaction strength λ0 exceeds a critical value. We study systems of different particle numbers and interaction strength and find that even if the overall ground state is collapsed there is a plethora of fragmented excited states that are still in the metastable region. Utilizing the configuration interaction expansion we determine the spectrum of the ground (“yrast”) and excited many-body states with definite total angular-momentum quantum numbers 0⩽L⩽N and −L⩽ML⩽L, and we find and examine states that survive the collapse. This opens up the possibility of realizing a metastable system with overcritical numbers of bosons in a ground state with angular momentum L≠0. The multiorbital mean-field theory predictions about the existence of fragmented metastable states with overcritical numbers of bosons are verified and elucidated at the many-body level. The descriptions of the total angular momentum within the mean-field and the many-body approaches are compared.